2020
DOI: 10.3390/geriatrics5010014
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Status and Outcomes of Older People in Orthopedic Rehabilitation? A Retrospective-Cohort Study

Abstract: Background: Cognitive function of older people is not routinely assessed in orthopedic rehabilitation, after elective and non-elective surgery. The aim of this study was to assess cognitive impairment and its impact on both length of stay and functional outcomes, of older people admitted to orthopedic rehabilitation. Methods: Retrospective audit, inclusion criteria: aged >65 years, orthopedic diagnosis, discharged from hospital. Results: 116 files were audited, mean age of 82.3 (SD = 7.5) years. Diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The median age of participants in our study is consistent with data from a systematic review of randomized controlled trials of inpatient geriatric rehabilitation, which reported mean ages of participants in the included studies ranging from 74.2 to 86.0 2 . In addition, the final cohort of 251 patients over a 1-yr period constitutes one of the larger chart reviews of geriatric rehabilitation populations, which have abstracted data from between 116 and 215 charts 3,4,33,35 . As with most chart abstraction, the data relied on accurate documentation by nurses, physicians, and allied health members, which may be subject to human error and lead to exposure misclassification of certain variables.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The median age of participants in our study is consistent with data from a systematic review of randomized controlled trials of inpatient geriatric rehabilitation, which reported mean ages of participants in the included studies ranging from 74.2 to 86.0 2 . In addition, the final cohort of 251 patients over a 1-yr period constitutes one of the larger chart reviews of geriatric rehabilitation populations, which have abstracted data from between 116 and 215 charts 3,4,33,35 . As with most chart abstraction, the data relied on accurate documentation by nurses, physicians, and allied health members, which may be subject to human error and lead to exposure misclassification of certain variables.…”
Section: Discussionsupporting
confidence: 77%
“…I npatient geriatric rehabilitation has been shown to improve function, reduce admission to long-term care, and reduce mortality when compared with usual inpatient care without rehabilitation. 1,2 The majority of rehabilitation literature on older adults focuses on specific patient populations-including orthopedic, [3][4][5][6] oncology, 7 and stroke. 8,9 However, the bulk of the current literature focuses on rehabilitation candidates and outcomes on the basis of their diagnosis, rather than a general older adult population who experiences a hospitalization.…”
mentioning
confidence: 99%
“…25 Relationships with MoCA scores and functional rehabilitation outcomes have been reported for patients with lower extremity amputations 5 and patients with hip fracture. 1 Recently Marks and colleagues (2021) found that the MoCA was more sensitive than the BIMS in predicting impairments in instrumental ADLs (iADLs; including checkbook balancing and shopping tasks) among older community dwellers. 26 Identification of patients who may have difficulty with functional and instrumental ADLs is important in creating a safe home discharge plan for patients and caregivers following an IRF stay.…”
Section: Introductionmentioning
confidence: 99%
“…Patient cognition is affected not only by the acute injury or illness leading to hospitalization but is often layered on top of delirium, mild cognitive disorders, or dementia that may or may not have been diagnosed previously. Impaired cognition is common not only for patients recovering from stroke or brain injury, but patients with hip fracture, 1,2 coronary heart disease, 3 chronic obstructive pulmonary disease, 4,5 and lower extremity amputations 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation